Dimensi Pengawasan pada Tindak Lanjut Laporan Pengaduan Masyarakat kepada Komisi Kejaksaan dalam Tinjauan Hukum Progresif - R Muhamad Ibnu Mazjah (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2020)
Presidential Decree No. 18 of 2011 on the Prosecutors Commission of the Republic of Indonesia (PCRI) does not contain textual procedural law provisions regarding follow-up reports on public complaints. This raises a question of whether the PCRI has the authority to carry out direct examinations and investigations as part of its authority to follow up public complaints. Based on the provisions of Articles 4 a and 4 b of the Presidential Decree No. 18 of 2011, it is acknowledged that after PCRI received public complaints, PCRI has two options in exercising its authority, namely carrying out a direct follow-up or forwarding these public complaints to the Attorney General and have it followed-up by internal supervisors. However, the absence of written or textual provisions in the Presidential Decree No. 18 of 2011 regarding this matter has resulted in the interpretation that PCRI is not authorized to conduct direct examinations, inspections, and investigations. This encourages the author to interpret that the authority of the PCRI in carrying out the follow-up on public complaints is based on a progressive legal perspective. This writing uses a normative research method, which aims to obtain legal arguments about the dimensions of supervision as a follow-up to public complaint reports. This paper is expected to introduce a reasoned discussion of PCRI in carrying out the supervisory duties. At the end part of this paper, there are recommendations regarding the need for regulatory authority as reinforcement for PCRI in carrying out supervisory duties and its authority to impose sanctions in the event of non-compliance. At the operational level, it is necessary to have a common perception shared between PCRI and Prosecutors of the Republic of Indonesia to create synergy in carrying out supervisory duties. AbstrakPerpres Nomor 18 Tahun 2011 tentang Komisi Kejaksaan RI (KKRI) tidak memuat secara tekstual ketentuan hukum acara tentang tindak lanjut laporan pengaduan masyarakat (lapdumas). Hal ini menimbulkan pertanyaan, apakah KKRI memiliki kewenangan melakukan pemeriksaan dan pengusutan secara langsung sebagai bagian dari kewenangan menindaklanjuti lapdumas. Berdasarkan ketentuan Pasal 4 a dan 4 b Perpres No. 18 Tahun 2011 dapat diketahui bahwa setelah KKRI menerima lapdumas, KKRI memiliki dua opsi kewenangan yakni menindaklanjuti secara langsung atau meneruskan lapdumas tersebut kepada Jaksa Agung untuk ditindaklanjuti pengawas internal. Namun, tidak adanya ketentuan tertulis di dalam Perpres No. 18 Tahun 2011, menimbulkan tafsir KKRI tidak berwenang melakukan pemeriksaan, pengusutan, penyelidikan secara langsung. Hal ini mendorong penulis untuk menafsirkan kewenangan KKRI dalam menindaklanjuti lapdumas berdasarkan perspektif hukum progresif. Penulisan ini menggunakan metode penelitian normatif, yang bertujuan untuk mendapatkan argumentasi hukum tentang dimensi pengawasan sebagai tindak lanjut laporan pengaduan masyarakat. Tulisan ini diharapkan dapat berdaya guna dalam pengembanan tugas pengawasan oleh KKRI. Di bagian akhir, tertuang rekomendasi mengenai perlunya pengaturan kewenangan sebagai penguatan bagi KKRI dalam menjalankan tugas pengawasan serta kewenangan penjatuhan sanksi apabila terjadi ketidakpatuhan. Pada tataran operasional, diperlukan penyamaan persepsi antara KKRI dengan Kejaksaan RI agar tercipta sinergitas dalam menjalankan tugas pengawasan.